Bacterial Communities of the Uterus and Rumen During Heifer Development With Protein Supplementation - Ault-Seay, Taylor B.; Brandt, Kiernan J.; Henniger, Madison T.; Payton, Rebecca R.; Mathew, Daniel J.; Moorey, Sarah E.; Schrick, F. Neal; Pohler, Ky G.; Smith, Timothy P. L.; Rhinehart, Justin D.; Schneider, Liesel G.; McLean, Kyle J.; et al. (Frontiers in Animal Science, 2022)
Bacterial communities play major roles in rumen and uterine function toward optimal animal performance and may be affected by changes occurring during heifer development such as nutritional supplementation for optimal growth and the attainment of puberty. The effect of different levels of protein supplementation on ruminal and uterine bacterial communities following weaning was examined through first breeding of heifers. Angus heifers (n = 39) were blocked by initial body weight (BW) and randomly assigned to one of three 163-day (d) crude protein (CP) supplementation diets including control (10% CP, n = 14), 20% CP (n = 11), or 40% CP (n = 14) treatment groups. Growth and development were monitored by body weight, with blood progesterone concentration determined every 14 d to determine pubertal status. Uterine flush and rumen fluid were collected on d 56, 112, and 163 relative to the start of supplementation. Bacterial DNA was extracted from fluid samples, the V1–V3 hypervariable region of the 16S rRNA gene was amplified, and amplicons were sequenced then processed in R 4.1. Statistical analyses were performed in SAS 9.4 with a GLIMMIX procedure utilizing fixed effects of protein, month, pubertal status, and interactions, with random effects including BW, interaction of BW and protein, and heifer within the interaction, and repeated measures of day. In the uterus, pubertal status and day of supplementation affected the observed amplicon sequence variants (ASVs) and led to clustering of samples in a principal coordinate analysis (PCoA; P < 0.05), but no effect of protein supplementation was observed. Ruminal samples clustered in PCoA (P = 0.001), and observed ASVs were impacted over time (P < 0.0001), but no effect of protein supplementation was detected. In contrast, protein supplementation, pubertal status, and day of supplementation affected the abundance of multiple phyla and genera in the uterus and rumen (P < 0.05). Temporal and pubertal status effects on the heifer’s uterine bacterial communities potentially indicate a maturing uterine microbiome. Protein supplementation did not impact microbial diversity measures but did affect the abundance of individual bacterial phyla and genera that may provide future opportunities to manipulate bacterial community composition and maximize productivity.